The Expression and Possible Functions of Tenascin-W During Development and Disease - Tucker, Richard P.; Degen, Martin (Frontiers in Cell and Developmental Biology, 2019)
Tenascins are a family of multifunctional glycoproteins found in the extracellular matrix of chordates. Two of the tenascins, tenascin-C and tenascin-W, form hexabrachions. In this review, we describe the discovery and domain architecture of tenascin-W, its evolution and patterns of expression during embryogenesis and in tumors, and its effects on cells in culture. In avian and mammalian embryos tenascin-W is primarily expressed at sites of osteogenesis, and in the adult tenascin-W is abundant in certain stem cell niches. In primary cultures of osteoblasts tenascin-W promotes cell migration, the formation of mineralized foci and increases alkaline phosphatase activity. Tenascin-W is also prominent in many solid tumors, yet it is missing from the extracellular matrix of most adult tissues. This makes it a potential candidate for use as a marker of tumor stroma and a target for anti-cancer therapies.